2017
DOI: 10.1186/s12941-017-0215-z
|View full text |Cite
|
Sign up to set email alerts
|

A pre-therapeutic coating for medical devices that prevents the attachment of Candida albicans

Abstract: BackgroundHospital acquired fungal infections are defined as “never events”—medical errors that should never have happened. Systemic Candida albicans infections results in 30–50% mortality rates. Typically, adhesion to abiotic medical devices and implants initiates such infections. Efficient adhesion initiates formation of aggressive biofilms that are difficult to treat. Therefore, inhibitors of adhesion are important for drug development and likely to have a broad spectrum efficacy against many fungal pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 55 publications
(64 reference statements)
0
23
1
Order By: Relevance
“…Since the publication of the original report first describing them, mutations in MRR2 have been referenced as a clinically relevant mechanism of fluconazole resistance (30)(31)(32). While our results confirm that artificial activation of the Mrr2 ZCF indeed results in CDR1 upregulation and a consequent increase in fluconazole resistance as previously described (14), we were unable to replicate the changes attributed to these mutations in a previous report (28).…”
Section: Discussioncontrasting
confidence: 45%
“…Since the publication of the original report first describing them, mutations in MRR2 have been referenced as a clinically relevant mechanism of fluconazole resistance (30)(31)(32). While our results confirm that artificial activation of the Mrr2 ZCF indeed results in CDR1 upregulation and a consequent increase in fluconazole resistance as previously described (14), we were unable to replicate the changes attributed to these mutations in a previous report (28).…”
Section: Discussioncontrasting
confidence: 45%
“…Adsorption of filastatin on dental resin and silicone showed that Candida cell attachment was reduced on these materials by 62.7 and 79.7%, respectively, compared to uncoated controls. By incorporating filastatin into the silicone matrix during polymerization a 6.5-fold reduction in C. albicans adhesion compared to untreated silicone controls was observed (Vargas-Blanco et al, 2017). Other small molecule biofilm inhibitors specifically interrupt Candida quorum sensing.…”
Section: Preventing Candida Biofilms Using Surface Modification With mentioning
confidence: 99%
“…One example, filastatin, a potent small molecule inhibitor of Candida attachment and filamentation was recently identified in a screen of 30,000 compounds (Fazly et al, 2013). Vargas-Blanco et al (2017) found that incubation of C. albicans with various biomaterials in the presence of filastatin can inhibit Candida attachment to these materials. Adsorption of filastatin on dental resin and silicone showed that Candida cell attachment was reduced on these materials by 62.7 and 79.7%, respectively, compared to uncoated controls.…”
Section: Preventing Candida Biofilms Using Surface Modification With mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Filastatin was discovered using C. elegans as a live host and has been shown to alleviate disease and improve nematode survival to levels comparable to fluconazole [129] using the C. elegans infection model. Furthermore, Filastatin-coated surfaces have been shown to decrease C. albicans adhesion [134].…”
Section: C Elegans As a Model Host To Study Virulence Of C Albicansmentioning
confidence: 99%